PENGARUH MOTIVASI KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA PT. GUNUNG RAJA PAKSI - Tajudin, Hanif; Thamrin, Djuni; Siahaan, Matdio (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of work motivation and work culture on employee performance at PT. Gunung Raja Paksi. This study employed a descriptive quantitative approach, with data collection using a questionnaire distributed to 105 respondents. A purposive sampling technique was used to determine the sample, and the collected data were analyzed using the statistical tool Smart Partial Least Squares (SmartPLS) 4. The results indicate that work motivation has a significant influence on employee performance. High motivation can increase enthusiasm, initiative, and productivity in completing work. Furthermore, work culture has also been shown to significantly influence performance, where positive values ​​such as discipline, cooperation, and responsibility create a conducive work environment and support the achievement of optimal performance. These findings emphasize the importance of internal factors within an organization in improving the overall quality of employee work.